The Role of the ILO in Resolving Violence Against Indonesian Crew on Fishing Vessels - Yordan Gunawan; Andi Pramudya Syamsu (Universitas Lampung, 2023)
In response to reports that seafarers on fishing boats in different parts of the world were being forced to work, the International Labor Organization (ILO) created and adopted ILO Convention No. 188 of 2007. It sets rules for dangerous work in the large fishing industry. It also covers the protection of crew on fishing vessels from exploitation and injury while doing work. Protection of crew on fishing vessels is essential due to acts of violence against Indonesian workers on fishing vessels owned by China and Taiwan that resulted in many Indonesian workers losing their lives. The purpose of the research is to find out the role of the ILO and the Government of Indonesia as the country of origin of crew fishing vessels in solving the problem of violence against crew fishing vessels. The study uses qualitative research methods by collecting information from relevant sources such as conventions, journals, legal texts, and other works related to the main research topic. While Indonesia has a law on the protection of migrant workers and has adopted the ILO Convention 111 concerning Discrimination in Respect of Employment and Occupation, neither are sufficient to address the issue. Thus, the role of the ILO is urgently needed to work hand-in-hand with all countries in the world to deal with this problem globally and encourage member states to ratify ILO Convention 188 especially Indonesia, since Indonesia is the biggest archipelagic country where most of the people are fishermen and crew on fishing vessels belonging to other countries.